Navigating the 12% VAT Increase in Indonesia: Challenges and Opportunities for Equity Investors in the Context of Islamic Finance - Insirat, Mutahira Nur; Syahfir, Hasri Ainun; Darmawati, Darmawati; Rasyid, Syarifuddin (Universitas Muhammadiyah Makassar, 2025)
This study examines the economic and investment implications of Indonesia’s Value Added Tax (VAT) increase from 11% to 12%, effective January 1, 2025, within the framework of Islamic finance. The policy, part of a broader fiscal reform, aims to enhance state revenue, promote sustainable development, and strengthen fiscal stability, while applying the higher rate only to luxury goods and services. Using an exploratory qualitative approach, this research analyzes both challenges and opportunities arising for equity investors in the Indonesian capital market. Findings reveal that the VAT increase may reduce consumer purchasing power, particularly affecting consumption-driven sectors such as consumer goods and retail, thereby increasing market volatility and reducing short-term profitability. However, sectors less affected by the policy such as healthcare, technology, and halal finance present diversification opportunities aligned with Shariah principles. From an Islamic finance perspective, taxation is permissible when implemented with fairness (‘adl) and aimed at public welfare (maslahah), ensuring that vulnerable groups remain protected. The study highlights that investors integrating Shariah ethics, risk management, and sustainability considerations can navigate fiscal adjustments more effectively. Overall, the VAT increase, while posing short-term market challenges, may lead to long-term fiscal resilience and responsible investment opportunities under a just and transparent Islamic economic framework.